Analisa Faktor Yang Berhubungan Dengan Status Gizi Balita Di Kabupaten Sragen - Isnani Nurhayati; Anas Rahmad Hidayat (Interest : Jurnal Ilmu Kesehatan, 2019)
Background: Nutrition problems in Indonesia are a major problem in human development because nutritional status reflects the quality of the nation itself. Monitoring of Nutritional Status in 2015 showed that toddlers according to the weight index per age obtained 79.7% good nutrition; 14.9% malnutrition and 3.8% malnutrition and 1.5% over nutrition. The data shows that the presence of children under five has a status of poor or poor nutrition. Kalijambe Subdistrict, Sragen Regency in 2012 there were still under-fives with one status of malnutrition with 29 toddlers (30%) out of a total of 3,452 toddlers. Method: Type of study was analytic descriptive with approach Cross-Sectional. The population was all mothers of children under five, the sampling technique with probability sampling is the number of respondents 50 mothers of children under five. Data analysis using chi-square. Results: There was a significant relationship between the education of mothers of children under five with the nutritional status of children (p = 0.0001 <0.05). There was a significant relationship between maternal knowledge of children under five and the nutritional status of children under five (p = 0.035 <0.05). Conclusion: There was no relationship between the number of children under five with the nutritional status of children (p = 0.49) and there was no relationship between the number of families with the nutritional status of children (p = 0.85). So that the factors that affect toddler nutrition in Jetiskarangpung Village, Sragen is education and mother's knowledge.